Protective Effects of Phytochemical Antioxidants Against Neurotoxin-Induced Degeneration of Dopaminergic Neurons - Taizo Kita; Masato Asanuma; Ikuko Miyazaki; Mika Takeshima (Elsevier, 2014)
The specific toxicity to dopaminergic neurons of psychostimulants and neurotoxins has been extensively studied in vivo and in vitro, and findings have been used to establish animal models of amphetamine psychosis or Parkinson's disease. The multiple mechanisms of neurotoxicity operating in these disorders are known to involve oxidative stress or neuroinflammation, producing the characteristic behavioral and neuropathlogical changes arising from injured dopaminergic neurons and glial cells. A number of studies have shown that glia-targeting antioxidants play important roles in protecting against the neurotoxicity caused by psychostimulants or neurotoxins. Phytochemicals, which are non-nutritive plant chemicals, protect dopaminergic neurons and glial cells from damage caused by psychostimulants or neurotoxins. The objective of this review was to evaluate the involvement of glial cells in dopaminergic neuron-specific toxicity and to explore the neuroprotective activity of phytochemicals in terms of anti-inflammatory and antioxidant action. Keywords:: dopaminergic neurotoxicity, psychostimulant, neurotoxin, phytochemical